CNS Lupus Presenting As Encephalitis : A Case Report - Azad, KAK; Sardar, MH; Appolo, AM; Mallik, MU; Sarker, M (Journal of Dhaka Medical College, 2011)
An 18 years old female presented with several episodes of convulsions followed by unconsciousness. On admission, her Glasgow Coma Scale was 3, and other neurological and systemic examination revealed no abnormality. Initially it appeared to be a case of viral encephalitis with a background probability of glomerulonephritis. Differential diagnosis was uraemic encephalopathy and seizure disorder. However, finally it was diagnosed as a case of CNS Lupus - a rare presentation of Systemic Lupus Erythematosus (SLE). Key words: Convulsion; glomerulonephritis; encephalitis; lupus. DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8588 J Dhaka Med Coll. 2011; 20(1) :82-85